Archie - Gordon, Domenica More (Bloomsbury, 2012)
Archie, a fashion-loving dog with a faithful pet of his own, leads a quiet life until he gets a sewing machine and begins creating canine couture that captures attention all over town, even from a queen and her two royal corgis.